B cells maturation in infancy and its affect in early allergy - Karlsson, Emma (My University, 2019)
The last decades, the presence of allergy has increased in countries belonging to the Western world and over 25 % of Swedish young people are aﬀected of allergic symptoms. One reasonable explanation is the hygiene hypothesis, mentioned by David Strachan 1989, that associate the increase in allergy development with a cleaner lifestyle. Previous studies showed that children who grew up on a farm with animals had a more maturated immune system and therefore developed less allergy. With samples received from the study named Nutritional impact on Immunological maturation during Childhood in relation to the Environment(NICE),I have studied the B cells maturation during early time in life. By studying subpopulations of B cells, speciﬁc surface markers are stained with ﬂuorochromes to be analysed with a ﬂow cytometer. Thus, the development of B cell subpopulations from birth up to 4 months can be charted. Several surface markers can indicate the same subpopulation, i.e. CD27+ and CD24hiCD38lo that are expressed by memory B cells. However, the percentage diﬀer from each other and the most liable reason is that the surface markers have diﬀerent functions in the B cells, and are therefore not only expressed during one phase of the development of B cells. My results shows that the development of percentage of subpopulations of B cells diﬀer from each other from birth up to 4 months. Correlation tests indicate that CD27+ and CD24hiCD38lo could both be used to detect memory B cells. Correlation tests at number of subpopulations had higher correlation coeﬃcient and were strongly signiﬁcant at birth. Therefore, it would be interesting to continue the analysis of numbers of B cells populations at 48h, 1, 4 and 12 months of life. In the NICE study, so far 452 children have been examined for allergy and 6.2 % suﬀered from eczema, 2.4 % of food allergy and 6.2 % of the children had developed asthmaat1yearofage. Inthisthesis, there was no signiﬁcant associations between B cell maturity and the development of allergy.
Keywords: Livsvetenskaper; Immunologi; Immunologi inom det medicinska området; Medicinsk bioteknologi (med inriktning mot cellbiologi); Life Science; Immunology; Immunology in the medical area; Medical Biotechnology (with a focus on Cell Biology)